Transdisciplinary Learning Based on Problem Identification of Design Computational Thinking - A Case Study of the Topic of Marine Debris - Chung-Hsiang Wang; Ko-Chiu Wu (Journal of Advanced Research in Social Sciences and Humanities, 2023)
Aim: The purpose of this study is to explore how design students can identify marine debris problems and generate insights through the computational thinking learning process to better develop design students’ ability to learn across domains. Methodology: Authors set up a transdisciplinary learning course of